2020
DOI: 10.1101/2020.10.29.20222430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence of common mental disorders among health care professionals during the COVID-19 pandemic at a tertiary Hospital in East Africa

Abstract: Background: Coronavirus disease 2019 (COVID-19) has resulted in unprecedented morbidity, mortality, and health system crisis leading to a significant psychological distress on healthcare workers (HCWs). The study aimed to determine the prevalence of symptoms of common mental disorders among HCWs during the COVID-19 pandemic at St. Paul Hospital, Ethiopia. Methods: A self-administered cross-sectional study was conducted to collect socio-demographic information and symptoms of mental disorders using validated m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…According to our study, Health care providers living with their spouse and family were more likely to develop depression than those HCPs living alone. This finding is supported by research findings in St Paul, Ethiopia [ 64 ], Saudi Arabia [ 55 ], India [ 75 , 84 ], and the United Kingdom [ 87 ]. which states that HCWs who were either married or married with children were more depressed than those among unmarried HCWs/ living alone [ 84 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to our study, Health care providers living with their spouse and family were more likely to develop depression than those HCPs living alone. This finding is supported by research findings in St Paul, Ethiopia [ 64 ], Saudi Arabia [ 55 ], India [ 75 , 84 ], and the United Kingdom [ 87 ]. which states that HCWs who were either married or married with children were more depressed than those among unmarried HCWs/ living alone [ 84 ].…”
Section: Discussionsupporting
confidence: 75%
“…Mali (73.3%) [ 53 ], Saudi Arabia (51.4%) [ 54 ], (78.8%) [ 55 ], Iran (67.55%) [ 56 ], Iraq (48.9%) [ 57 ], Nepal (41.9%) [ 58 ], Turkey (45.1%) [ 59 ], China (41.1%) [ 60 ], (44.6%) [ 4 ], North Italy (50.1%) [ 61 ], and USA (43%) [ 62 ]. However, it is higher than the study conducted in St Peter hospital, Addis Ababa (21.2%) [ 63 ], St Paul Hospital (21.9%) [ 64 ], multinational multi-center study (8.7%) [ 65 ], Middle East country (23.6%) [ 66 ], Iran (25.8%) [ 67 ], China 8.5% [ 68 ] (14.3%) [ 69 ], India (17.7%) [ 47 ], Italy (19.8%) [ 70 ], Malaysia (29.7%) [ 71 ], and Australia (21%). This discrepancy may be due to differences in workload, socioeconomic, cultural, and environmental factors, variation in the availability of personal protective equipment and resources, the difference in emotional response related to previous experience/exposure with SARS, MERS, and H1N1 epidemics, and also it may be related to the different cut-off scores used to define levels of clinically significant anxiety.…”
Section: Discussionmentioning
confidence: 62%
“…the finding from Hubei province, Wuhan in China among healthcare workers exposed to 2019 Coronavirus disease found that the prevalence of psychological distress was 71.2% (13). In other ways, the magnitude of the psychological distress among healthcare workers during the COVID-19 pandemic in Ethiopia ranges from 42% (14) in Dessie city to 78.3% (15) in Jimma town.…”
Section: Introductionmentioning
confidence: 98%
“…The total number of respondents in these studies was 5,323. The qualitative study had the least 50 respondents [37], while the most signi cant number of participants, 422, was recorded in one of the studies from Ethiopia [38]. The response rates varied between 90%-100%, with most studies dominated by male respondents, 51.9%-69.2%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Age of over 40 years was associated with moderate to severe symptoms of PTSD. Two studies concluded that respondents aged over 40 years were more likely to develop PTSD symptoms than their younger counterparts [37,41]. 3.4.2 Gender: Female gender was signi cantly associated with depression, anxiety, and stress symptoms among HCWs in 07 of the studies reviewed [36][37][38][41][42][43].…”
Section: Study Characteristicsmentioning
confidence: 99%